International Survey on Bioenergy Knowledge, Perceptions, and Attitudes Among Young Citizens - ÇAKIR, MUSTAFA (SPRINGER, 2012)
The present study with an international perspective, investigated the state of knowledge, perceptions, and attitudes among young students toward bioenergy in Finland, Slovakia, Taiwan, and Turkey. A total of 1,903 students with an average age of 15 years from 19 rural and urban schools participated in this study. The study found statistically significant differences in students' bioenergy knowledge with respect to the countries. Only a small percentage of the students in each country were able to demonstrate a high level of bioenergy knowledge. In overall, the gender and rural-urban differences did not play a significant role in determining students' level of bioenergy knowledge. The students appeared to be very critical of bioenergy and especially of the issues related to bioenergy production from forests. They demonstrated positive attitudes in terms of their willingness to learn about bioenergy and its use in their daily life. The study found statistically significant effects of gender and locality on students' perceptions of bioenergy. Most knowledgeable students in bioenergy appeared to be most critical in their perceptions and attitudes toward bioenergy. The principal component analysis revealed three distinct dimensions of students' perceptions and attitudes toward bioenergy viz., motivation, critical, and practical. A broader societal support is needed for the introduction of bioenergy in many countries and young generation's positive attitudes to this matter is certainly important for people who will create policies in this area. More efforts are needed to support young students so that they understand the multi-dimensional issues related to bioenergy by allowing them to have practical experiences with bioenergy.
Keywords: Bioenergy; Knowledge; Perceptions; Attitudes; Young citizens; SCHOOL-STUDENTS ATTITUDES; GENDER-DIFFERENCES; RENEWABLE ENERGY; ENVIRONMENTAL ATTITUDES; SCIENCE; BIOFUELS; VIEWS; PARTICIPATION; EFFICIENCY; BEHAVIORS